2005
DOI: 10.1007/s00122-004-1813-7
|View full text |Cite
|
Sign up to set email alerts
|

A combination of AFLP and SSR markers provides extensive map coverage and identification of homo(eo)logous linkage groups in a sugarcane cultivar

Abstract: Sugarcane varieties are complex polyploids carrying in excess of 100 chromosomes and are derived from interspecific hybridisation between the domesticated Saccharum officinarum and the wild relative S. spontaneum. A map was constructed in Denotes variety covered by Australian plant breeding rights., an Australian cultivar, from a segregating F1 population, using 40 amplified fragment length polymorphism (AFLP) primer combinations, five randomly amplified DNA fingerprints (RAF) primers and 72 simple sequence re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
100
0
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(112 citation statements)
references
References 27 publications
1
100
0
11
Order By: Relevance
“…SSRs are ideal markers that exhibit great precision in polymorphism, reproducibility, multi-allelic nature and their transferability across genera (Parida et al 2010;Devarumath et al 2012). It also helps in breeding process including germplasm fingerprinting, genetic mapping and marker-assisted selection (Aitken et al 2005). Recently, microsatellites have been used to set up the genetic map in Saccharum spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSRs are ideal markers that exhibit great precision in polymorphism, reproducibility, multi-allelic nature and their transferability across genera (Parida et al 2010;Devarumath et al 2012). It also helps in breeding process including germplasm fingerprinting, genetic mapping and marker-assisted selection (Aitken et al 2005). Recently, microsatellites have been used to set up the genetic map in Saccharum spp.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, microsatellites have been used to set up the genetic map in Saccharum spp. (Aitken et al 2005) as well as other poacea crops. Microsatellites or SSRs are categorized into the genomic (gSSR) and gene based Expressed Sequence Tags (EST-SSRs).…”
Section: Introductionmentioning
confidence: 99%
“…Due to high level of heterozygosity and complexity of its genome, sugarcane molecular research has been confronted with unique challenges not encountered in other major crops, resulting in a slow progress in sugarcane molecular breeding. Nonetheless, many researchers have made an effort to evaluate different sources of sugarcane germplasm with various DNA markers, including 5S rRNA intergenic transcribed spacer (ITS) [1], restriction fragment length polymorphism (RFLP) [2] [3], random amplified polymorphic DNA (RAPD) [4] [5] [6] [7], amplified fragment length polymorphism (AFLP) [8] [9] [10], simple sequence repeats (SSR) [8] [11] [12] [13] [14], target region amplification polymorphism (TRAP) [15] [16], conserved-intron scanning marker (CISP) [17] [18] and single nucleotide polymorphism (SNP) [19] [20]. Sugarcane breeders have successfully found some cultivarspecific, species-specific and trait-specific DNA makers to accelerate the breeding process [13] Among PCR-based marker systems, SSR is a powerful marker system once developed for a particular organism due to its ubiquitous distribution across the entire genome, high polymorphism, and reliability.…”
mentioning
confidence: 99%
“…Molecular markers are widely used in plant genetic diversity as a result of not affected by environment. So far, different molecular markers, such as target region amplified polymorphism (Que et al, 2009), restriction fragment length polymorphism (Daugrois et al, 1996;Grivet et al, 1996), amplified fragment length polymorphism (Cai et al, 2005;Aitken et al, 2005Aitken et al, , 2006, random amplified polymorphic DNA (RAPD) (Mudge et al, 1996;Tabasum et al, 2010), and simple sequence repeat (SSR) (Pan, 2006;Santos et al, 2012), have been used in studies on the genetic diversity of sugarcane. As we know, single molecular markers are more often used when developing this research; very few studies on genetic diversity of sugarcane have reported using a combination of two or more molecular markers, especially in China.…”
Section: Introductionmentioning
confidence: 99%